Novel Cu(II)–EDTA Decomplexation by Discharge Plasma Oxidation and Coupled Cu Removal by Alkaline Precipitation: Underneath Mechanisms - Wang, Tiecheng; Cao, Yang; Qu, Guangzhou; Sun, Qiuhong; Xia, Tianjiao; Guo, Xuetao; Jia, Hanzhong; Zhu, Lingyan (Environmental science & technology, 2018)
Strong complexation between heavy metals and organic complexing agents makes the heavy metals difficult to be removed by classical chemical precipitation. In this study, a novel decomplexation method was developed using discharge plasma oxidation, which was followed by alkaline precipitation to treat water containing heavy metal–organic complex, that is, Cu–ethylenediaminetetraacetic acid (Cu–EDTA). The decomplexation efficiency of Cu complex reached up to nearly 100% after 60 min’s oxidation by discharge plasma, which was accompanied by 82.1% of total organic carbon removal and energy efficiency of 0.62 g kWh–1. Presence of free Cu2+ favored Cu–EDTA decomplexation, whereas the presence of excessive EDTA depressed this process. Cu–EDTA decomplexation was mainly driven by the produced 1O2, O2 •–, O3, and •OH by discharge plasma. Cu–EDTA decomplexation process was characterized by UV–vis, ATR–FTIR, total organic carbon, and three-dimensional fluorescence diagnosis. The main intermediates including Cu–EDDA, Cu–IDA, Cu–NTA, small organic acids, NH4 +, and NO3 – were identified, accompanied by Cu2+ releasing. The followed precipitation process removed 78.1% of Cu2+, and Cu-associated precipitates included CuCO3, Cu2CO3(OH)2, CuO, and Cu(OH)2. A possible pathway of Cu complex decomplexation and Cu2+ removal in such a system was proposed.